Quantum Molecular Polyhedra and Atomic Populations - Carbó-Dorca, Ramon (Scientific World, 2021)
The present paper uses the LCAO MO theory formalism. The structure of the first order electronic density function is decomposed in two kinds of quantum polyhedra to discuss the behavior of quantum atomic populations. Among the many aspects one can consider about atomic populations here, the quantum mechanical structure of the density function is taken as the most important characteristic to think about. Apart of the usual one-electron basis set, centered in the molecular atoms, there is also discussed the possibility that the three-dimensional space where the molecular structures are described can be also the site of basis functions centered in points non-coincident with atomic positions.